2005
DOI: 10.1103/physrevb.72.115418
|View full text |Cite
|
Sign up to set email alerts
|

Radial-breathing-like phonon modes of double-walled carbon nanotubes

Abstract: The radial-breathing-like phonon modes (RBLMs) of the double-walled carbon nanotubes are studied in a simple analytical model, in which the interaction force constants (FCs) can be obtained analytically from the continuous model. The RBLMs frequencies are obtained by solving the dynamical matrix, and their relationship with the tube radii can be obtained analytically, offering a powerful experimental tool for determining precisely the radii of the multi-walled carbon nanotubes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The theory calculation shows that when uniaxial strain increases, the frequencies of RBM mode almost do not change, while the G band are downshifted linearly. 28 Furthermore, the linear shifting rate of Raman modes under uniaxial strain is almost the same for SWNTs with different diameters. 29 Figure 4a are the scanning Raman spectroscopic maps plotting G + band frequency.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The theory calculation shows that when uniaxial strain increases, the frequencies of RBM mode almost do not change, while the G band are downshifted linearly. 28 Furthermore, the linear shifting rate of Raman modes under uniaxial strain is almost the same for SWNTs with different diameters. 29 Figure 4a are the scanning Raman spectroscopic maps plotting G + band frequency.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…In order to further characterize the properties of the suspended SWNTs, the Raman spectra were measured. The theory calculation shows that when uniaxial strain increases, the frequencies of RBM mode almost do not change, while the G band are downshifted linearly . Furthermore, the linear shifting rate of Raman modes under uniaxial strain is almost the same for SWNTs with different diameters …”
Section: Resultsmentioning
confidence: 87%
“…Using the simple analytical model presented in Ref. 94 and by assuming the carbon atoms on the nanotube wall to be distributed continuously, Wu et al 95 investigated the RBLMs of the DWCNTs. Based on the continuum model presented by Wu and Dong, 96 Wu and co-workers 95,96 derived a set of formulae to describe the interaction between an infinite-length nanotube and an atom in any place.…”
Section: Radial Breathing-mode Of Carbon Nanotubesmentioning
confidence: 99%
“…94 and by assuming the carbon atoms on the nanotube wall to be distributed continuously, Wu et al 95 investigated the RBLMs of the DWCNTs. Based on the continuum model presented by Wu and Dong, 96 Wu and co-workers 95,96 derived a set of formulae to describe the interaction between an infinite-length nanotube and an atom in any place. After that, the influence of matrix on the frequencies of RBLMs of MWCNTs was carried out by using a spring coefficient defined by the Winkler model.…”
Section: Radial Breathing-mode Of Carbon Nanotubesmentioning
confidence: 99%
“…They observed that the change of the transformation time from RBM to CFM due to the variation of the perturbation velocity field. Although some studies of Raman RBM of double-or multi-walled CNTs also have been carried out using continuum mechanics (Wu et al, 2007;Wang & Ru, 2005;Han & Goddard, 2009;Popov & Henrard, 2002) these analytical models were discussed theoretically and there was a lack of experimental investigation. Popov and Henrard (2002) studied the breathinglike phonon modes of MWCNTs using a valence force field model.…”
Section: Introductionmentioning
confidence: 99%